Estimation of Wind Power Density at a Wind Farm Site Located in Western Rajasthan Region of India. (2016) - Saxena, Bharat Kumar; Rao, K.V.S.
Abstract: Wind power density is an important parameter for the potential estimation of a wind farm and is used to compare different sites. This paper estimates wind power density of Soda site located at Western Rajasthan in India. Modified Maximum Likelihood, Empirical, and Graphical methods are used for estimating Weibull distribution parameters, which are used for calculating wind power density. The calculated wind power density is then compared with actual measured values for validation. The results obtained using Empirical method shows better agreement with the measured data of wind power density.